A Cytoskeletal Platform for Local Translation in Axons - Van Horck, Francisca P. G. (2008)
Recent data indicate that local translation in growth cones is critical for axon guidance. Evidence from the Drosophila midline axon guidance system suggests that the F-actin-microtubule cross-linker Short stop (Shot) might link the translation machinery to the cytoskeleton in the growth cone. The identification of a complex of translation factors attached to the actin and microtubule networks points to a mechanism by which cytoskeletal dynamics regulate translation in axons and vice versa.